Effect Of Routing Packet Overheads On Routing Protocols (International Journal of Engineering and Computer Science, 2017)
Mobile Ad-Hoc networks (MANETs) are collection of mobile nodes that dynamically forming a temporary network without preexisting network infrastructure and communicate with its neighbors to perform peer to peer communication and transmission. It offers unique benefits and versatility for certain environments and certain applications. Since there is no prerequisite fixed infrastructure and base stations, they can be created and used anytime, anywhere. Propagation models focused on predicting the average received signal strength at a given distance from the transmitter, as well as the variability of the signal strength in close spatial proximity to a particular location. The accuracy of any particular propagation model in any given condition will depend on the suitability among the constraints required by the model and depend on terrain. A number of propagation models like Free Space and Two Ray ground have been exist. In this paper, we present comparative study on the behavior of various routing protocols with path loss propagation models, various performance metrics used for this comparison such as packet delivery fraction, average jitter, throughput and average end to end delay. The studies would be helpful in choosing the correct protocol for any active operating environment.